The influence of green surface modification of oil palm mesocarp fFiber by superheated steam on the mechanical properties and dimensional stability of oil palm mesocarp fiber/poly(butylene succinate) biocomposite - Then, Yoon Yee; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Ariffin, Hidayah; Wan Yunus, Wan Md. Zin; Chieng, Buong Woei (MDPI, 2014)
In this paper, superheated steam (SHS) was used as cost effective and green processing technique to modify oil palm mesocarp fiber (OPMF) for biocomposite applications. The purpose of this modification was to promote the adhesion between fiber and thermoplastic. The modification was carried out in a SHS oven at various temperature (200-230 °C) and time (30-120 min) under normal atmospheric pressure. The biocomposites from SHS-treated OPMFs and poly(butylene succinate) (PBS) at a weight ratio of 70:30 were prepared by melt blending technique. The mechanical properties and dimensional stability of the biocomposites were evaluated. This study showed that the SHS treatment increased the roughness of the fiber surface due to the removal of surface impurities and hemicellulose. The tensile, flexural and impact properties, as well as dimensional stability of the biocomposites were markedly enhanced by the presence of SHS-treated OPMF. Scanning electron microscopy analysis showed improvement of interfacial adhesion between PBS and SHS-treated OPMF. This work demonstrated that SHS could be used as an eco-friendly and sustainable processing method for modification of OPMF in biocomposite fabrication.